Organizational climate: a study in a small porte foundation in Claudio (Research, Society and Development, 2020)
The organizational climate represents the level of satisfaction of people in the workplace. Organizational climate research provides insight into the factors that motivate or demotivate employees in an organization. Thus, this article aims to analyze the factors that influence the organizational climate in a small foundry in the city of Claudio, MG. A descriptive case study was conducted, adopting the qualitative and quantitative approaches. Data collection was done by questionnaires applied to 95% of employees. The results indicate that the factors that most influence the organizational climate in a positive way are: adequate working environment and conditions, the employee performs the function according to his / her profile, job stability, best quality of life at work, benefits offered by the company, good relationship between team people, agility in company decisions, recognition for work performed, information received about their work, the company being open to new ideas, organizational structure. The factors that negatively influence him are: inadequate leadership style, ineffective communication, lack of training, lack of career advancement opportunities, lack of criteria for internal promotion, and unequal treatment of employees by leaders. Thus, the results revealed important information for the company, which can contribute to its repositioning in relation to meeting the needs of employees, which may contribute to increase their satisfaction with the work.